2005
DOI: 10.2174/092986705774454733
|View full text |Cite
|
Sign up to set email alerts
|

Based on HLA-DRβ1* Allele Binding Specificities, Striking Differences in Distance and TCR Contacting Residue Orientation can be Observed in Modified Protection-Inducing Malarial Synthetic Peptides

Abstract: An anti-malarial vaccine is urgently needed, especially against P. falciparum which causes 2 to 3 million deaths each year, mostly in Sub-Saharan African children. This vaccine should contain molecules from the parasite's different developmental stages due to the parasite's remarkable complexity and genetic variability. The first approach using synthetic peptides from different parasite stage molecules (the SPf66 malaria vaccine) conferred limited protective efficacy in Aotus monkeys and in large field-trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 126 publications
(237 reference statements)
1
9
0
Order By: Relevance
“…One of the most important observations to emerge from such study has been that conserved HABPs have poor antigenicity, poor immunogenicity and poor or no protection-inducing activity, thereby making them silent to a host's immune system. Our results have also shown that each specifically identified HABP's immunological properties have been directly related to its 3D structure [5,14,16,71,106]. This has suggested a strong correlation between binding (functional approach), 3D structure and immune response (biological activity).…”
Section: Structural Considerations For Rendering Conserved Habps Antisupporting
confidence: 61%
See 3 more Smart Citations
“…One of the most important observations to emerge from such study has been that conserved HABPs have poor antigenicity, poor immunogenicity and poor or no protection-inducing activity, thereby making them silent to a host's immune system. Our results have also shown that each specifically identified HABP's immunological properties have been directly related to its 3D structure [5,14,16,71,106]. This has suggested a strong correlation between binding (functional approach), 3D structure and immune response (biological activity).…”
Section: Structural Considerations For Rendering Conserved Habps Antisupporting
confidence: 61%
“…Our results with merozoite-modified HABPs has shown that such modifications have resulted in better presentation and binding to MHC molecules and the formation of a more stable TCRpeptide-MHC (TCR-p-MHC) complex, highlighting these specifically-modified HABPs potential as components of a fully-effective antimalarial vaccine [5,14,16,84,106].…”
Section: Components Of a Fully-effective Minimal Subunit-based Antimentioning
confidence: 82%
See 2 more Smart Citations
“…41,44,[50][51][52][53][54][55][56][57][58] This distance was 6.5 ( 0.5 Å and 4.5 ( 1.5 Å shorter in short-lived and long-lasting antibody-inducing but non-protection-inducing modified HABPs, respectively, than in immunogenic, protection-inducing ones; residue orientation was also different. 42,43 In essence, immunogenic protection-inducing modified conserved HABPs have been modified so that they can fit perfectly into the MHC II-peptide-TCR complex for triggering an appropriate immune response, providing tremendous support for using chemically synthesized, specifically modified conserved HABPs in vaccine development.…”
Section: Structural and Binding Characteristics Of Hla-dr Moleculesmentioning
confidence: 90%